Weight components in pirapitinga (Piaractus brachypomus) (Cuvier, 1818) (Teleostei: Characidae) in the floodplain of Arauca, Colombia - Parés-Casanova, Pere M. (2023)
The aim of this study was to estimate the allometric parameters of different parts of pirapitinga (Piaractus brachypomus), as well as to establish if the growth of these components is allometric or isometric. In total, 60 specimens collected at random from a farm in Arauca (Colombia) were used. Live weights, carcass weights and weights of scales, viscera and gills were determined. Three algorithms were tested to quantify the relationships between live body weight and each of the components: Ordinary Least Squares, Reduced Major Axis, and Major Axis. The data were logarithmically transformed in order to fit the equations to the allometric function y=10bxa, where y represents the body component in question and x is the independent associated variable. The three methods provided regression coefficients that are, from a theoretical point of view, different, thus providing different estimates of the same quantity. The Ordinary Least Squares algorithm, with the minimum slope, would appear to be the model that best fits the real allometric behavior of this species.